Clinical characteristics and risk factors of postoperative pneumonia after hip fracture surgery: a prospective cohort study. Issue 10 (October 2016) - Lv, H.; Yin, P.; Long, A.; Gao, Y.; Zhao, Z.; Li, J.; Zhang, L.; Zhang, L.; Tang, P.
Abstract Summary In this study, we attempt to determine the clinical characteristic and risk factors of postoperative pneumonia (POP) after hip fracture surgery in a well-defined hip fracture cohort. We find that intrinsic factors as well as major clinical interventions were all important risk factors of POP. Introduction Postoperative pneumonia (POP) is one of the major complications following hip fractures surgery. However, the risk factors of POP are not well studied in hip fracture cohorts. We attempt to determine the clinical characteristic and risk factors of POP after hip fracture surgery in a well-defined hip fracture cohort. Methods Datasets from a prospective hip fracture cohort study with a 2-year follow-up period, from 2000 to 2011, were reanalyzed for characteristics of POP. Multivariate Cox proportional regression was used to evaluate the association between the incidence of POP and all-cause mortality. Multivariate logistic regression was used to screen for potential risk factors of POP by analyzing demographic factors, comorbidities, major clinical interventions, and hematological parameters. Results In 1429 patients who underwent hip surgery, the incidence of POP was 4.9 % (n = 70). All-cause mortality of patients with POP was significantly higher than that of patients without POP at 30 days (hazard ratio (HR) 3.05, 95 % confidence intervals (CI) 1.88–4.94), 1 year (HR 1.87, 95 % CI 1.41–2.48), and 2 years (HR 1.57, 95 % CI 1.23–1.99) postoperatively. Multivariate logistic regression showed that intrinsic factors (advanced age, anemia, diabetes, prior stroke, number of comorbidities, ASA score ≥III, and some laboratory biomarkers) as well as major clinical interventions were all significant risk factors for POP. Conclusion Intrinsic factors and major clinical interventions were all important risk factors of POP in patients after hip fracture surgery. Targeted preventive measures to mitigate the above risk factors may help in reducing the incidence of POP.